Association of socio-demographic and specific causative factors associated with development of cataract: a cross-sectional study - Raut, Pritish K.; Gupta, Sachin; Burungale, Shamkumar U. (International Journal Of Community Medicine And Public Health, 2020)
Background: Cataract is a major cause of blindness worldwide, particularly so in India. Cataract constitutes 55% of total blindness in this country. It is generally acknowledged that age-related (senile) cataract is a multifactorial disease. The combined effect of these risk factors can help in better prediction of cataract as compared to their individual effects and is also helpful in determining preventive and curative interventions in development of cataract. Objective: To study the association between development of cataract and specific causative factors, socio-demographic factors. Methods: 274 patients diagnosed with cataract were interviewed with the help of a pre tested interview schedule. Results: Total of 274 cases was included in the study, of which 126 (46%) were male and 148 (54%) were female. Illiterate females being more prone for the development of cataract (p value=0.001). There are more than double the chances of developing cataract in people who are exposed to U-V radiation (OR=2.14). Out of total cases, 156 (56.9%) cases were having present or past history of addiction in the form of tobacco and the significant association was found between tobacco consumption and development of cataract (p value=0.012). Conclusions: Improvement in knowledge, literacy level and protection against U-V radiation will be helpful to reduce morbidity of senile cataract among elderly people.